Value of Peptide Receptor Radionuclide Therapy as Neoadjuvant Treatment in the Management of Primary Inoperable Neuroendocrine Tumors - Opalińska, Marta; Sowa-Staszczak, Anna; Grochowska, Anna; Olearska, Helena; Hubalewska-Dydejczyk, Alicja (Frontiers in Oncology, 2021)
Introduction Neuroendocrine neoplasms including neuroendocrine tumors (NET) are often diagnosed as primary disseminated or inoperable. In those cases, systemic extensive therapy is necessary, but radical treatment is unlikely. As described in the literature, in some selected cases, Peptide Receptor Radionuclide Therapy (PRRT) may be used as a first-line/neoadjuvant therapy that allows further successful surgery. Such treatment may enable a reduction of total tumor burden or allow a radical treatment which improves the final outcomes. Aim Assessment if the neoadjuvant PRRT could be a treatment option for patients with initially unresectable NETs. Methods Among the group of 114 patients treated with PRRT in years 2005-2020, in over 30 cases it was the first-line therapy, mainly due to massive disease burden at the time of diagnosis. Among them, 9 patients received PRRT as the first-line treatment due to the primary inoperable tumors with the intention of preoperative reduction of the tumor size in order to allow for a surgical treatment. Results Neoadjuvant PRRT enabled surgery in 4 out of 9 (45%) patients. Finally, in 2 cases (22%) the goal (radical surgery) has been achieved. Conclusion PRRT may be considered not only as a palliative, but also as a neoadjuvant therapy in advanced, somatostatin positive NETs, that were initially inoperable.